Clinical rationale of sucroferric oxyhydroxide for controlling hyperphosphatemia in patients with chronic kidney disease. (January 2015) - Sprague, Stuart M; Marcuccilli, Morgan; Rakov, Viatcheslav
Sucroferric oxyhydroxide (Velphoro ®, Vifor Fresenius Medical Care Renal Pharma Ltd) is an iron-based phosphate binder approved for the control of serum phosphorus concentrations in chronic kidney disease patients receiving dialysis. Clinical data indicate that sucroferric oxyhydroxide has similar efficacy to sevelamer carbonate in lowering serum phosphorus levels; however, with a substantially lower pill burden with on average three to four pills/day versus eight to nine pills/day of sevelamer carbonate. Sucroferric oxyhydroxide is associated with discolored feces, as expected for oral iron-based compounds. Some patients reported mild and transient diarrhea, mostly at the start of treatment, which did not require any interventions. There is minimal iron absorption, without risk of iron overload. Overall, sucroferric oxyhydroxide is an effective, well-tolerated new treatment for managing hyperphosphatemia in dialysis patients.